2020
DOI: 10.1101/2020.08.09.20171041
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A city-level analysis of air pollution, climate and COVID-19 early spread during the Spanish lockdown

Abstract: The COVID-19 outbreak has escalated into the worse pandemic of the present century. The rapid spread of the new SARS-CoV-2 coronavirus has caused devastating health and economic crises all over the world, with Spain being one of the worst affected countries in terms of confirmed COVID-19 cases and deaths per inhabitant. In this situation, the Spanish Government declared the lockdown of the country with the aim of flattening the epidemic curve. The variations of air pollution in terms of fine particulate matter… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…On the other hand, inconsistent results were reported from a study assessing the correlation between urban air pollution in the Milan metropolitan area and number of COVID-19 deaths, which found a negative correlation with air pollution assessed through surface levels of both PM 2.5 and PM 10 (Zoran et al, 2020b), and ground levels of nitrogen dioxide (Zoran et al, 2020a), but a positive one using ground levels of ozone, possibly due to the enhanced formation of outdoor airborne secondary aerosols (Zoran et al, 2020a). Similarly, a study of seven Spain cities found little association between outdoor air pollutant levels as assessed through traffic monitoring stations and COVID-19 transmission (Briz-Redon et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, inconsistent results were reported from a study assessing the correlation between urban air pollution in the Milan metropolitan area and number of COVID-19 deaths, which found a negative correlation with air pollution assessed through surface levels of both PM 2.5 and PM 10 (Zoran et al, 2020b), and ground levels of nitrogen dioxide (Zoran et al, 2020a), but a positive one using ground levels of ozone, possibly due to the enhanced formation of outdoor airborne secondary aerosols (Zoran et al, 2020a). Similarly, a study of seven Spain cities found little association between outdoor air pollutant levels as assessed through traffic monitoring stations and COVID-19 transmission (Briz-Redon et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…Higher COVID-19 mortality was also correlated with relatively poor air quality in several other countries (Pansini and Fornacca, 2020). However, results from some recent studies have been inconsistent, with some reporting a null (Bontempi, 2020b;Briz-Redon et al, 2020) or inverse association (Zoran et al, 2020a) between air pollution and SARS-CoV-2 infection incidence. Therefore, this putative correlation appears to be worthy of further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological evidence associates chronic PM 2.5 exposure to health problems [9; 10; 11]. Nonetheless, in a recent study, researchers did not observed association between PM 2.5 exposures with COVID-19 transmission during the rst months of the pandemic [12].…”
Section: Introductionmentioning
confidence: 94%
“…Indeed, epidemiological evidence associates chronic PM 2.5 exposure with health problems [9][10][11]. Nonetheless, in a recent study, researchers did not observe an association between PM 2.5 exposure and COVID-19 transmission during the first months of the pandemic [12].…”
Section: Introductionmentioning
confidence: 93%